2020
DOI: 10.3168/jds.2019-17256
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis modulates the biosynthesis of inflammatory lipid mediators derived from linoleic acid in adipose tissue of periparturient dairy cows

Abstract: Oxidized linoleic acid metabolites (OXLAM) are products of adipocyte lipolysis with the potential to modulate adipose tissue (AT) lipid metabolism and inflammation. In periparturient cows, linoleic acid is preferentially mobilized from AT during lipolysis by hormone-sensitive lipase (HSL) compared with other polyunsaturated fatty acids. Enzymatic and nonenzymatic reactions generate OXLAM from linoleic acid. Among OXLAM, 9-, 10-, and 12-hydroxy-octadecadienoic acids (HODE) are associated with pro-inflammatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Pharmacological ISO treatment of 3T3-L1 cells and adipose tissue in mice stimulated lipolysis and release of fatty acids (Chitraju et al, 2017). A similar effect was detected in adipose tissue of periparturient dairy cows where incubation with ISO induced the activity of HSL and increased release of linoleic acid (Andres Contreras et al, 2020). This effect was confirmed in the present study through the increased abundance of ATGL, the ratio of p-HSL to HSL, and the glycerol content along with decreased abundance of PLIN1 in calf adipocytes.…”
Section: Discussionmentioning
confidence: 74%
“…Pharmacological ISO treatment of 3T3-L1 cells and adipose tissue in mice stimulated lipolysis and release of fatty acids (Chitraju et al, 2017). A similar effect was detected in adipose tissue of periparturient dairy cows where incubation with ISO induced the activity of HSL and increased release of linoleic acid (Andres Contreras et al, 2020). This effect was confirmed in the present study through the increased abundance of ATGL, the ratio of p-HSL to HSL, and the glycerol content along with decreased abundance of PLIN1 in calf adipocytes.…”
Section: Discussionmentioning
confidence: 74%
“…A comprehensive characterization of OS during the periparturient period or health events in AT of dairy cows is currently lacking. However, there is evidence for the presence of OS in AT of these cows as we detected isoprostanes, the gold standard OS biomarker, in AT during the first three weeks after calving [125].…”
Section: Redox Signaling and Dairy Cows' Lipid Mobilizationmentioning
confidence: 76%
“…In the meantime, plasma 9-HODE remained unchanged (Contreras et al, 2017a). When we evaluated the production of HODE in AT during the PP, we found that HSL activity is determinant in the synthesis of these oxylipids (Contreras et al, 2020). Most importantly, HSL releases linoleic acid for HODE biosynthesis in concentrations of a magnitude that may bypass the need for the activation of phospholipases linked with the inflammatory cascade, and thus supports, in part, lipolysis-driven inflammation within AT of periparturient cows.…”
Section: Lipid Mediators Of Inflammation In At Of Dairy Cowsmentioning
confidence: 88%
“…Both enzymatic and nonenzymatic (FR mediated) oxidative reactions yield oxylipids that rapidly modulate inflammatory responses within AT. Remarkably, lipolysis significantly increases the content of oxylipids in the AT of healthy rodents and cows (Gartung et al, 2016;Contreras et al, 2020).…”
Section: Lipid Mediators Of Inflammation In At Of Dairy Cowsmentioning
confidence: 99%